Pengaruh Brand Image, Brand Trust, Brand Awarnes terhadap Brand Loyalty Telkomsel di kalangan Mahasiswa - Anggraeni, Sinta (Indonesian Journal of Strategic Management, 2022)
This research aims to determine the impact of brand image, brand trust, and brand awareness on Telkomsel's brand loyalty among students. The technique used to take samples using purposive sampling. The population and sample are limited to STIE Surakarta students with the criteria that respondents have used Telkomsel for approximately one year and respondents are active students at STIE Surakarta. The data that has been collected were analyzed by validity test, reliability test, classical assumption test, and multiple linear regression analysis. The study resulted in a statement that the variables of brand image, brand trust, and brand awareness had no significant impact on Telkomsel's brand loyalty among STIE Surakarta students.